Where She Went - Forman, Gayle (London Definitions Publishers, 2012)
Adam, now a rising rock star, and Mia, a successful cellist, reunite in New York and reconnect after the horrific events that tore them apart when Mia almost died in a car accident three years earlier.
Keywords: Rock music -- Emotional problems of teenagers -- First loves